Specialty Meat Marketing Claims: What's the Difference? - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS, 2008)
AN-191, a 6-page illustrated report by Chad Carr, Larry Eubanks, and Ryan Dijkhuis, discusses production/marketing claims defined by the USDA and addresses the differences between these products for food safety, human health, and eating quality. Includes references. Published by UF Department of Animal Sciences, September 2007. Reviewed February 2008.